Multiple Consequences Induced by Epidermally-Located Anthocyanins in Young, Mature and Senescent Leaves of Prunus - Lo Piccolo, Ermes; Landi, Marco; Pellegrini, Elisa; Agati, Giovanni; Giordano, Cristiana; Giordani, Tommaso; Lorenzini, Giacomo; Malorgio, Fernando; Massai, Rossano; Nali, Cristina; Rallo, Giovanni; Remorini, Damiano; et al. (Frontiers in Plant Science, 2018)
Anthocyanic morphs are generally less efficient in terms of carbon gain, but, in turn, are more photoprotected than anthocyanin-less ones. To date, mature leaves of different morphs or leaves at different developmental stages within the same species have generally been compared, whereas there is a lack of knowledge regarding different stages of development of red vs green leaves. Leaves (1-, 7-, and 13-week-old) of red- (RLP) and green-leafed (GLP) Prunus in terms of photosynthetic rate, carbon metabolism and photoprotective mechanisms were compared to test whether anthocyanin-equipped leaves perform better than anthocyanin-less leaves and whether photoprotection is the primary role of epidermally-located anthocyanins, using for the first time a recently-developed parameter of chlorophyll fluorescence (qPd). GLP leaves had a higher photosynthetic rate in 1- and 7-week-old leaves, but RLP leaves performed better at an early stage of senescence and had RLP had a longer leaf lifespan. Anthocyanins contributed to leaf photoprotection throughout the leaf development, but were tightly coordinated with carotenoids. Besides photoprotecting, we propose that epidermal anthocyanins may be principally synthetized to maintain an efficient carbon-sink strength in young and senescent leaves, thus extending the RLP leaf lifespan.